2003
DOI: 10.1088/0953-8984/15/23/310
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance and electron–nuclear double-resonance study of Ticentres in KTiOPO4

Abstract: Electron paramagnetic resonance and electron–nuclear double resonance have been used to characterize four Ti3+ centres in undoped crystals of potassium titanyl phosphate (KTiOPO4 or KTP). These 3d1 defects (S = 1/2) are produced by ionizing radiation (either 60 kV x-rays or 355 nm photons from a tripled Nd:YAG laser), and form when the regular Ti4+ ions in the crystal trap an electron. Two of these trapped-electron centres are only observed in hydrothermally grown KTP and the other two are dominant in flux-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Some of observed EPR lines have spin-Hamiltonian characteristics, which are close to the parameters described Cr 3+ and Fe 3+ [1][2][3]. However, many lines do not belong to paramagnetic centers, which were identified previously [4][5][6][7][8][9][10]. Intensities of additional EPR lines, which appeared after γ-irradiation, correlated with the concentrations of non-controlled impurities.…”
Section: Wwwpss-ccommentioning
confidence: 59%
“…Some of observed EPR lines have spin-Hamiltonian characteristics, which are close to the parameters described Cr 3+ and Fe 3+ [1][2][3]. However, many lines do not belong to paramagnetic centers, which were identified previously [4][5][6][7][8][9][10]. Intensities of additional EPR lines, which appeared after γ-irradiation, correlated with the concentrations of non-controlled impurities.…”
Section: Wwwpss-ccommentioning
confidence: 59%
“…The crystals properties can be modified by the impurities, e. g., transition-metal and rareearth ions, thus affecting the applications. Hence, the spectroscopic studies of KTP crystals doped by impurities, which can provide information on the impurity energy levels, the defect models and structures in the doped crystals, have received significant attention [10][11][12][13][14][15][16][17]. Bravo et al, [17] measured the EPR spectra of W-doped KTP crystal and found two approximately rhombic W 5 þ centers, which belong to the first-kind rhombic center defined in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The g matrix and the hyperfine matrices obtained from the resulting electron paramagnetic resonance (EPR) and electronnuclear double resonance (ENDOR) spectra then verify the existence of an alkali vacancy next to the unpaired spin. Trapped holes located next to potassium vacancies have been observed in KTP crystals [15][16][17], and Laruhin et al [18] have suggested that similar hole centers associated with rubidium vacancies are produced in RTP crystals.…”
Section: Introductionmentioning
confidence: 99%